Faith beyond reason - Evans, C. Stephen (Edinburgh University Press, 1998)
Can a 'leap' of faith be justified? Ought we not to reject anything for which there is no evidence? C. Stephen Evans distinguishes between a faith which rejects all reason and a faith requiring that reason is self-critical. In this accessible book he addresses this central debate in the philosophy of religion in the light of the key arguments from Kierkegaard, Aquinas and Kant. The text leads the student gently through the traditional topics, such as knowledge of God's existence, the problem of evil, and how someone could know that his or her religion had been based on revelation from God.
Keywords: Kierkegaard, Søren, -- 1813-1855 -- Religion.; Kierkegaard, Søren, -- 1813-1855; Faith and reason -- Christianity.; RELIGION -- Faith.; Faith and reason -- Christianity; Religion; Godsdienst.; Rationaliteit.; Fideïsme.